2003
DOI: 10.1021/es020848i
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polar Organic Compounds in the Organic Film on Indoor and Outdoor Glass Windows

Abstract: Organic films on an impervious surface (window glass) were sampled at paired indoor-outdoor sites in July 2000 and characterized for their paraffinic and polar organic compositions along an urban-rural transect. Four classes of polar compounds (C11-C31 aliphatic monocarboxylic, C6-C14 dicarboxylic, nine aromatic polycarboxylic, and five terpenoid acids) constituted between 81 and 95% (w/w) of the total organic fraction analyzed comprising n-alkanes (C10-C36), 46 PAH, 97 PCBs, and 18 OC pesticides. Concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 48 publications
7
139
1
Order By: Relevance
“…SAMs formed by reaction of trichloroalkylsilanes on SiO x surfaces, for example on the thin oxide layer on silicon, may be particularly relevant to reactions of organic compounds on dust and on building materials for which silicates can be major components. 208,[238][239][240][241][242][243][244] Another advantage is that silicon crystals are readily available which can be used to make real-time measurements of the oxidation of SAMs attached to their surface using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. In one study, 221 ozonolysis of terminal alkene SAMs with 3-and 8-carbon atoms was observed to give CQO groups as products as expected, at least a portion of which were in the form of carboxylic acids that could be converted to carboxylates by reaction with gaseous NH 3 .…”
Section: This Journal Is C the Owner Societies 2009mentioning
confidence: 99%
“…SAMs formed by reaction of trichloroalkylsilanes on SiO x surfaces, for example on the thin oxide layer on silicon, may be particularly relevant to reactions of organic compounds on dust and on building materials for which silicates can be major components. 208,[238][239][240][241][242][243][244] Another advantage is that silicon crystals are readily available which can be used to make real-time measurements of the oxidation of SAMs attached to their surface using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. In one study, 221 ozonolysis of terminal alkene SAMs with 3-and 8-carbon atoms was observed to give CQO groups as products as expected, at least a portion of which were in the form of carboxylic acids that could be converted to carboxylates by reaction with gaseous NH 3 .…”
Section: This Journal Is C the Owner Societies 2009mentioning
confidence: 99%
“…The few existing studies on this topic show that organic films can range from 11 to 1000 nm in thickness and that the proportion of organic matter ranges from approximately 5e20% (Diamond et al, 2000;Liu et al, 2003b;Wu et al, 2008). Due to the high proportion of organic content of the film, the concentrations of semi-volatile organic compounds (SVOCs) are high on the artificial surfaces of urban areas (Butt et al, 2004;Gingrich et al, 2001;Liu et al, 2003a). SVOCs can accumulate in organic films through the exchange and partitioning of gasphase chemicals with air and/or the direct deposition of particlephase compounds (Diamond et al, 2000;Law and Diamond, 1998;Liu et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Consistent with the results of laboratory studies, increased HONO levels have been measured during dust storms. 28 Organic compounds are also known to be taken up on airborne dust particles 4,9,[29][30][31] and on building materials in the boundary layer, [32][33][34][35][36][37] and there is evidence that oxidation of organics occurs on these surfaces as well. 33,38,39 A number of the well-known surface-bound nitrogen oxides such as nitrite and nitrate ions photolyze in the actinic region 24 above 290 nm to form O À radical anions, which react with water to generate OH radicals.…”
Section: Introductionmentioning
confidence: 99%